2001
DOI: 10.1889/1.1831867
|View full text |Cite
|
Sign up to set email alerts
|

22.3: Diffuse Renditions of Spatially Pixelated and Temporally Multiplexed H‐PDLCs for Full Color Reflective Displays

Abstract: We report on incorporating a diffuse film into our spatial and angular multiplexing techniques to form Diffuse Holographicallyformed Polymer Dispersed Liquid Crystals (DHPDLC) using a single holographic exposure thus creating wide viewing angle multicolor reflective displays. Our work has resulted in a device with an increased viewing cone for wide viewing angle applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…This fact is supported by the narrow viewing angles of planar H-PDLCs observed in this work as well as in Ref. 4. Consequently, if the LC droplets are spherically shaped, with very little shape anisotropy and the walls of the droplet are smooth on the nanoscale, a high out-of-band transmission coefficient is observed.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This fact is supported by the narrow viewing angles of planar H-PDLCs observed in this work as well as in Ref. 4. Consequently, if the LC droplets are spherically shaped, with very little shape anisotropy and the walls of the droplet are smooth on the nanoscale, a high out-of-band transmission coefficient is observed.…”
Section: Discussionsupporting
confidence: 84%
“…Each plane-wave component of the spherical wave interferes with the planar reference wave to form a planar grating that has a grating vector given by (4) where k rz is the z component of the propagation vector of the reference wave. This expression is not a generalization: it is designed for the specific case of a reference wave propagating directly along the z-axis, as is found in our holographic set-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Bulk liquid crystal materials have previously been proposed in adaptable photomasking applications by Peng et al who suggested using a liquid crystal display as a light valve to control the resist curing UV light in the lithographic process. This film, or reflection grating, is formed from a homogeneous mixture of monomer, initiator, and liquid crystal uniformly spaced in an electrically conductive glass cell that has been exposed to an optical interference pattern created by two counterpropagating UV laser beams.…”
mentioning
confidence: 99%